Hernia Basecamp-A Free to Use, Online Hernia Learning Platform. Analysis of Its Use Since Launch in June 2021 - de Beaux, A; Becker, S; Parent, T; Temporal, G; Kummer, R; Allouard, C; East, B (Journal of abdominal wall surgery, 2023)
Introduction: Hernia Basecamp is an online learning platform hosted within the WebSurg website. One of the drivers of its development was to cover the syllabus of the UEMS AWS examination, but it is a learning resource in its own right. There are currently 205 video lectures, with a number of them selected to create 10 modules of 3 h each with UEMS CME accreditation. The aim of this study was to review the Hernia Basecamp usage since launch in June 2021. Methods: The Hernia Basecamp WebSurg platform was interrogated using Matomo Analytics in January 2023 (19 month period since launch). Data on the number of visits, pages looked at and time spent on the platform per visit, along with the number of CME modules taken and passed were collected. Results: Users from 146 countries visited the Hernia Basecamp site 17,171 times (6,586 times, 38.4% in first 9 months). The top 5 countries by visitors were the United Kingdom, Mexico, Spain, United States and Germany (accounting for 29.4% of the visits). The average time spent per visit was 11 min 37 s (range: 47 s-49 min 4 s), and the number of pages/videos viewed per visit was 8.1 (range: 2-21). The number of UEMS CME modules taken was 675, and 326 (48%) of these tests were passed. Conclusion: In the first 19 months from launch, Hernia Basecamp provided over 3,000 h of hernia education. The UEMS approved CME accreditation tests were commonly used.
Keywords: continuing medical education; education; UEMS; WebSurg; Hernia Basecamp